Sickle cell disease - Kunz, Joachim; Tagliaferri, Laura (Transfusion medicine and hemotherapy, 2024)
Background: Sickle cell disease (SCD) is among the most frequent hereditary disorders globally and its prevalence in Europe is increasing due to migration movements. Summary: The basic pathophysiological event of SCD is polymerization of deoxygenated sickle hemoglobin, resulting in hemolysis, vasoocclusion, and multiorgan damage. While the pathophysiological cascade offers numerous targets for treatment, currently only two disease-modifying drugs have been approved in Europe and transfusion remains a mainstay of both preventing and treating severe complications of SCD. Allogeneic stem cell transplantation and gene therapy offer a curative option but are restricted to few patients due to costs and limited availability of donors. Key Message: Further efforts are needed to grant patients access to approved treatments, to explore drug combinations and to establish new treatment options.
Online veröffentlicht: 6. August 2024
Gesehen am 24.03.2025